2015
DOI: 10.1007/s11277-015-2921-1
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Spectrum Occupancy Measurement for Cognitive Radio

Abstract: In order to support the ever growing demand of wireless communication systems and wireless local area network based 802.11 devices, the regulators are developing techniques to overcome the permanent scarcity of radio resources. Spectrum sensing in cognitive radio (CR) is considered as a key technology which estimates the availability of the licensed spectrum band for additional usages. The underutilized licensed band can be exploited among the secondary users provided that they would not cause any interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The two main factors that cause spectrum scarcity are as follows: (a) frequency bands are allocated to licensed users based on the traditional fixed spectrum assignment policy and (b) a huge volume of real-time data is generated and transferred over a wireless medium in a dynamic environment. The authors in [4] showed that most bands are still vacant and suitable for secondary usage.…”
Section: Introductionmentioning
confidence: 99%
“…The two main factors that cause spectrum scarcity are as follows: (a) frequency bands are allocated to licensed users based on the traditional fixed spectrum assignment policy and (b) a huge volume of real-time data is generated and transferred over a wireless medium in a dynamic environment. The authors in [4] showed that most bands are still vacant and suitable for secondary usage.…”
Section: Introductionmentioning
confidence: 99%
“…A CR is an intelligent software defined radio (SDR) that reconfigures its network parameters based on the network environment [9]. Preliminary work has shown that much of the licensed bands allocated to certain users are underutilized [10]. Unlicensed users, also called secondary users (SUs) can opportunistically access these underutilized radio frequency bands whenever the licensed users or primary users (PUs) are absent.…”
Section: Introductionmentioning
confidence: 99%
“…It has raised the demand of extra spectrum bands to solve the problems of spectrum scarcity. Due to static spectrum band allocation policy by the government agencies, some of the allocated spectrum bands are underutilized such as some portion of TV VHF/UHF bands, so-called TV white spaces [1][2][3][4]. To solve the problems of spectrum scarcity, US Federal Communication Commission (FCC) has suggested to use the underutilized spectrums and spectrum potions which are not in use, called vacant spectrum bands or white spaces [3].…”
Section: Introductionmentioning
confidence: 99%